Teknologi Informasi, Media Sosial, dan Transformasi Digital Terhadap Performa Usaha UMKM Laundry di Kota Batam - Surya Tjahyadi; Hendi Sama; Cindy Claudia Erica (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2026)
This study examines the effects of information technology, social media, and digital transformation on the business performance of laundry MSMEs in Batam City using a quantitative associative approach. Data were collected from 94 owners or managers of laundry MSMEs through questionnaires and analyzed using IBM SPSS Statistics 25. Classical assumption tests indicated that the data were normally distributed and free from multicollinearity and heteroscedasticity. Simultaneous testing showed that information technology, social media, and digital transformation jointly have a significant effect on business performance (F = 4.588; p = 0.005). However, partial test results revealed that only social media has a positive and significant effect on business performance, while information technology and digital transformation do not show significant effects. These findings suggest that in small-scale service MSMEs, market-oriented digital tools are more effective in improving business performance than complex internal technology adoption.